Investigation of the Relationship between Recreational Spor Well-Being and Leisure Satisfaction of University Community Members - Mustafa Sabır Bozoğlu; Yalçın Tükel; Ali Bayrak; Hasan Suat Aksu; Alper Kaya (Türk Spor ve Egzersiz Dergisi)
Only if there is time for sports is it possible for sports to give life significance. At this point, recreational sports take center stage. Recreational activities are known to improve health, but it is assumed that this health will also make leisure time more enjoyable. Accordingly, the purpose of this relational survey research is to evaluate the link between university community members' pleasure with their leisure time and recreational well-being. The research employed an easy random sampling procedure and a descriptive scanning methodology. In the study, "Recreational Sports Well-Being Scale" and "Leisure Satisfaction Scale" were used to determine the recreational sports well-being and leisure satisfaction levels of the participants. The universe of the research is "Selçuk University Student Societies". A total of 298 people participated in the research. As 14 participants left most of the questions blank and 7 participants marked more than one variable, 21 people were excluded from the study, and 277 people, 127 women and 150 men, were included in the study. The results show that there is a substantial relationship between leisure time satisfaction and the length of time spent engaging in recreational activities and sports. On the other hand, it has been determined that the income variable is one of the most effective factors in terms of well-being and leisure satisfaction. In conclusion; leisure satisfaction and recreational sport well-being are moderately positively related. It can be stated that the gains of female participants and participants with high perceived income from recreational sports activities contribute more positively to their well-being levels.